2014
DOI: 10.1021/bi5008904
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Induced RNA:DNA G-Quadruplex Structures Elicit an Anticancer Effect by Inhibiting Endogenous eIF-4E Expression

Abstract: RNA G-quadruplex (GQ) structures act as regulators of a diverse array of cellular processes including translation, pre-mRNA processing, and mRNA targeting. We report here a strategy of harnessing the natural ability of RNA GQs to inhibit translation by rationally inducing a GQ on a targeted mRNA to knockdown endogenous gene expression. We chose to target eIF-4E because of its key role in translation initiation and overexpression in multiple cancers and with the expectation that downregulation of eIF-4E would r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…It was reported that HQ formation could modulate transcription in vitro and in vivo, and their prevalence was recently evidenced . The spontaneous formation, within a model cell system, of HQ motifs between biologically relevant G‐rich mRNA sequences and a rationally designed extraneous synthetic G‐rich oligonucleotide was exploited as an elegant approach to repress gene translation and decrease the proliferation of cancer cells …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that HQ formation could modulate transcription in vitro and in vivo, and their prevalence was recently evidenced . The spontaneous formation, within a model cell system, of HQ motifs between biologically relevant G‐rich mRNA sequences and a rationally designed extraneous synthetic G‐rich oligonucleotide was exploited as an elegant approach to repress gene translation and decrease the proliferation of cancer cells …”
Section: Introductionmentioning
confidence: 99%
“…[11] The spontaneous formation, within am odel cell system, of HQ motifs between biologically relevant G-rich mRNA sequences and ar ationally designed extraneouss ynthetic G-rich oligonucleotidew as exploited as an elegant approach to repress gene translation and decrease the proliferationofc ancer cells. [12] The biological functiona ssociated with G4 nucleic acids has spurred al arge number of studies directedt owardt he identification of G4-specific binding probes and drugs. [13] Hundreds of distincts mall-molecule ligandsw ith high affinities toward DNA and RNA G4 motifs have been reported,a nd many have demonstrated the ability to affect cellular processes.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the cap-dependent translation initiation of the Renilla luciferase was inhibited specifically on knocking down eIF-4E, which in turn suggests the bicistronic nature of the construct. 12 It turned out that the lack of the GQ domain (mutants ΔD2 and ΔD123) significantly decreased IRES A activity (Figure 4; p < 0.001). The slight decrease in the activity of the ΔD1 mutant could be explained by its observed peripheral involvement in 40S binding.…”
Section: ■ Resultsmentioning
confidence: 90%
“…5 The plasmid was designed in a way such that one of the reporter genes (Firef ly luciferase) was translated in a cap-independent manner by IRES A whereas the other reporter gene (Renilla luciferase) initiates translation in the canonical pathway serving as the control ( Figure S9 of the Supporting Information). 5,12 Previously, we knocked down eIF-4E, the capbinding protein essential for canonical translation initiation, and when bicistronic plasmid hVEGFbicis activity was measured, a sharp decrease in the Renilla/Firef ly luciferase luminescence was observed. This indicates that the cap-dependent translation initiation of the Renilla luciferase was inhibited specifically on knocking down eIF-4E, which in turn suggests the bicistronic nature of the construct.…”
Section: ■ Resultsmentioning
confidence: 99%
“…To inhibit translation of the target mRNA, the fol lowing strategy was developed: formation of a bimolecu lar hybrid DNA-RNA G4 was initiated in the predeter mined regions of mRNA containing only two G tracts using modified oligodeoxyribonucleotides with design allowing targeted addition of missing G tracts required for G4 formation [397]. It was shown using the mRNA encoding eIF 4E protein, which was actively expressed in various malignant tumors, that formation of G quadru plexes in the 5′ UTR mRNA and in the protein coding region of the eIF 4E mRNA initiated by phosphoro thioate derivatives of oligonucleotides resulted in 30 and 60% inhibition of expression of this protein in human cancer cells, respectively [397]. On the contrary, addition of antisense oligonucleotides (complementary to the G4 motif) can result in the destruction of RNA G4 [398].…”
Section: Structural Features Of Rna Quadruplexes and Their Biologicalmentioning
confidence: 99%